Species composition and geographic distribution of Fuegian Curculionidae (Coleoptera: Curculionoidea) - Posadas, Paula (Zootaxa, 2012)
The objective of this paper is to provide an integrative approach to taxonomic composition and distributional informationon the weevil fauna (Coleoptera: Curculionoidea) of the Tierra del Fuego archipelago. A total of 39 species belonging to17 Curculionidae genera are recorded for the archipelago. Most of these belong to two subfamilies: Entiminae (13 speciesin four genera) and Cyclominae (23 species in 11 genera). Caneorhinus gravidus (Burmeister) is here established as a newjunior synonym of Caneorhinus lineatus (Blanchard). The Fuegian weevil fauna is considered to represent an impover-ished condition in comparison to that from continental southern South America. The Tierra del Fuego archipelago has noendemic genera of Curculionidae and only three species seem to be endemic to it (Antarctobius rugirostris Champion,Cylydrorhinus lateralis [Berg], and Cylydrorhinus fulvipes [Guérin-Méneville]). However, these three species have scarcerecords and more information is required to confirm their status as Fuegian endemics. No species present in Tierra delFuego extend their distribution beyond the Andean subregion. The Fuegian weevil fauna exhibits a great linkages to thatfrom continental southernmost South America. Synonymic lists and distributional maps are provided for each speciesknown to occur on the islands. Identification keys and photographs of weevil taxa recorded for Tierra del Fuego are also presented.